노후 압출기의 재제조를 위한 고장모드 영향분석 - 정항철(Hang-Chul Jung); 윤상민(Sang-Min Yun); 오상호(Sang-Ho Oh); 백창현(Chang Hyun Baeg); 공만식(Man-Sik Kong) (Clean Technology, 27(4), 2021)
In the domestic aluminum industry, the extrusion process is a major process accounting for more than 40% of the total production. However, most domestic aluminum extrusion companies produce aluminum using old equipment that is more than 30 years old. Extrusion press is when the equipment is not replaced before the wear and breakage of major parts occur, reducing productivity and increasing the defect rate compared to new equipment. The old extrusion press often loses part drawings, so it is difficult to repair them properly on-site and to remanufacture them due to the lack of technical skills for maintenance. Therefore, a systematic remanufacturing plan must be designed from dismantling the equipment. In this study, remanufacturing FMEA was devised to remanufacture old extrusion press. The risk priority was analyzed by considering the degree of damage to the recycled parts, the cycle due to breakage/damage during the extrusion process, and the value of recycling resources due to remanufacturing. To standardize the remanufacturing process, remanufactured FMEA was performed through part analysis according to the structural analysis of the extrusion press. In addition, remanufacturing priorities were selected for each part, while remanufacturing itself was studied for efficiency of resource circulation and product quality stabilization. 국내 알루미늄 산업에서 압출공정은 생산량 기준 40% 이상의 비중을 차지하고 있는 주요 공정이다. 국내 알루미늄 압출업체 대부분이 30년 이상 된 노후 설비를 이용하여 생산하고 있기 때문에 제품 정밀도 및 품질 저하, 낮은 생산성 등의 문제를 격고 있다. 압출 설비는 한번 도입하면 주요 부품의 마모 또는 파손 발생 전에는 설비를 교체하지 않는 구조로 신규 설비에 비해 생산성 감소 및 불량률이 증가하기 때문에 설비의 유지 관리가 중요하다. 노후 압출기는 부품의 도면이 소실된 경우가 많아 현장에서 적절한 보수가 어렵고 유지 관리를 위한 기술력 부재로 인해 재제조에 어려움을 겪고 있기 때문에 해체 단계에서부터 체계적인 재제조 방안이 고안되어야 한다. 본 연구에서는 노후 압출설비의 재제조를 위해 재제조 고장모드 영향분석 방법을 고안하였다. 부품에 대한 재제조 대상 부품의 파손에 대한 심각도, 압출 공정 중 고장/파손에 따른 수명 그리고 재제조에 따른 자원순환의 가치를 고려하여 위험우선순위를 산정하고 재제조 대상을 선정하였다. 노후 압출기의 재제조 공정의 표준화 정립을 위해 노후 압출기의 구조에 따른 모듈 및 부품에 대한 분석 등을 통해 재제조 고장모드 영향분석을 수행하였으며 부품별 우선순위를 선정하여 자원순환의 효율성 및 제품 품질 안정화를 위한 재제조 연구를 수행하였다.